(untitled) (Research, Society and Development, 2021)
The fishing activity generates a large amount of waste, seeking to reduce environmental impacts, it is possible to process the fish skin transforming it into leather. The objective of this was to evaluate the resistance of Nile tilapia hides in five slaughter weight categories, tanned with vegetable tannin, as well as using different levels of addition of vegetable tannin in the tanning process, for skins of the highest weight category. As the slaughter weight of the fish increased, there was an increase in thickness (Y=0.745990+0.044832X, R²= 88.27%), in progressive tear strength (Y= 0.735871+0.051553X, R²= 81.16%), in traction (Y=10.508074-1.847411X+0.664844X², R²=94.93%), in stretching (Y=58.112121+5.110606X, R²=84, 92%) and progressive tearing (Y=19.68836+7.800758X, R²= 84.83%), explained by the aforementioned equations. For fish skins above 1kg, 10% tannin was used in the tanning step and 4% in the retanning step and 12% and 2% tannin, respectively, for the tanning and retanning. Leathers in this size category showed greater tensile strength in the longitudinal direction. When analyzing the distribution of fine and thick collagen fibers regarding the direction of the leather, it was noted that tilapia leather has a higher proportion of fine fibers (62.40%) compared to thick (37.60%), this makes so that these are tied more intensely, providing greater resistance to the leather. The fine fibers provide a better binding of the histological structure of these leathers, generating greater resistance to traction, stretching and progressive tearing. It is concluded that the hides above fish above 1001g have greater thickness and strength quality to be used in confection.